INFLATIONARY EXPECTATIVES: PREDICTING, PERSISTENCE, AND DISAGREEMENT - Caetano, Sidney Martins; Silva Júnior, Geraldo Edmundo (Análise Econômica, 2012)
Because the expectations of inflation are considered a key-variable in the specification of macroeconomic models and due to the current discussion in literature on the disagreement concerning expectations, the present work aimed to study the divergence problem, starting from the statistical verification of the superior predicting ability of institutions that take part in the research (Focus- Market Report) of the Gerin/Bacen. The application of the SPA test, in short and long term analyses, suggested strength in the disagreement in the expectations of inflation, in which some models/institutions exert superior predicting ability. It is also possible to observe the presence of some degree of inertia in the dynamics of the expectations, in which the measures of persistence suggest sharp shock effects that diminish as time passes, in most of the cases analyzed.